2005
DOI: 10.1093/jn/135.6.1475
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Olive Vegetation Water in Mice Has Anti-Inflammatory Activity

Abstract: Fruit and vegetable simple and polyphenols are potent antioxidants. One of the most effective in terms of free radical scavenging is 3,4-dihydroxyphenyl ethanol or hydroxytyrosol (HT), a simple phenol found predominantly in Olea europea, or the olive plant. HT is most abundant in the aqueous fraction of olive pulp with trace amounts in the olive oil fraction and in the leaves. For these experiments, we evaluated the anti-inflammatory activity of olive vegetation water (OVW), which we showed previously to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 30 publications
4
108
0
Order By: Relevance
“…Inflammation is a complex process, which involves numerous mediators of cellular and plasma origins. Studies indicated that b-amyloid peptides 16) and hydrolyzed olive vegetation water 17) exhibited anti-inflammatory activities in human THP-1 cells. In this study, we showed that TET possessed potent anti-inflammatory activity on the same cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a complex process, which involves numerous mediators of cellular and plasma origins. Studies indicated that b-amyloid peptides 16) and hydrolyzed olive vegetation water 17) exhibited anti-inflammatory activities in human THP-1 cells. In this study, we showed that TET possessed potent anti-inflammatory activity on the same cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bitler et al [11] found that olive vegetation water highly enriched in HTyr (125 mg/mouse; 500 mg/kg) reduced serum TNF levels by 95% in LPS-treated mice. Gong et al [130] studied rats with acute inflammation induced by intravenous injection of carrageenan at 2% (w/v).…”
Section: In Vivo Htyr-mediated Anti-inflammatory Activity and Cancermentioning
confidence: 99%
“…Among biophenols, one of the most interesting is HTyr that has been widely studied demonstrating its numerous biological properties. This small molecule is a potent inhibitor of copper sulfateinduced LDL oxidation and of platelet aggregation (potentially reducing the risk of coronary heart disease and atherosclerosis) [4], acts as antioxidant and metal chelator in animal models [5], scavenges superoxide anion (O 2 .-) generated by either human polymorphonuclear cells or the xanthine/xanthine oxidase system [6], inhibits proliferation and induces apoptosis in HL-60 leukemia cells [7], prevents DNA damage and tyrosine nitration induced by peroxynitrite [8], protects toward hydrogen-peroxide (H 2 O 2 )-induced damage in human erythrocytes [9], inhibits passive smoking-induced *Address correspondence to these authors at the Università degli Studi della Tuscia, Dipartimento di Scienze e Tecnologie per l'Agricoltura, le Foreste, la Natura e l'Energia (DAFNE) oxidative stress [10], exhibits anti-inflammatory activity [11], exerts anti-microbial and anti-mycoplasmal activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokines, prostaglandins and NO, which are produced by monocytes and activated macrophages, play critical roles in inflammatory diseases such as atherosclerosis. VOO and hydrolysed olive vegetation water (Bitler et al, 2005) exhibit anti-inflammatory activities in the human monocytic leukemia cell line (THP-1). Previous studies have shown that, HT down-regulates iNOS and COX-2 gene expression in THP-1 cells (Zhang et al, 2009) and in murine macrophages by preventing NF-kB, STAT-1alpha (signal transducer and activator of transcription-1) and IRF-1 (interferon regulatory factor-1) activation (Maiuri et al, 2005).…”
Section: Postprandial Effect Of Olive Oil In Pbmncsmentioning
confidence: 99%